Roman amphorae in Neuss : Augustan to Julio-Claudian contexts - Berni Millet, Piero (Roman and late antique Mediterranean pottery, 2018)
The occupation of the territories on both sides of the Rhine was an enormous logistical challenge for the Roman military administration. This book provides an in-depth study of the amphorae from Neuss, providing further understanding of the local area and the logistics of the Roman army and its supply from very distant areas.